Neoantigen Specific T Cells Derived From T Cell-Derived Induced Pluripotent Stem Cells for the Treatment of Hepatocellular Carcinoma: Potential and Challenges - Lu, Fei; Ma, Xiao-Jing-Nan; Jin, Wei-Lin; Luo, Yang; Li, Xun (Frontiers in Immunology, 2021)
Immunotherapy has become an indispensable part of the comprehensive treatment of Hepatocellular Carcinoma (HCC). Whether it is in patients with early HCC, advanced HCC or HCC recurrence after liver transplantation, immunotherapy is effective. The most commonly used clinically are immune checkpoint monoclonal antibodies, such as CTLA-4 antibody and PD-1 antibody. However, it cannot fundamentally solve the problems of the weakened immune system and the inactivation of immune cells involved in killing tumor cells. T cells can express tumor antigen-recognizing T cell receptors (TCRs) or chimeric antigen receptors (CARs) on the cell surface through gene editing to improve the specificity and responsiveness of immune cells. Given that TCR-T cell therapy is significantly better than CAR-T cell therapy in the treatment of solid tumors, TCR-T cell therapy is one of the most promising immune cell therapies for solid tumors so far. However, its application in the treatment of HCC is still in the research stage. The maturity of induced pluripotent stem cells (iPSCs) induction and redifferentiation technology allows us to use T cells to induce T-iPSCs, and then differentiate them into TCR-T. It has provided us with a lot of convenience for studying HCC models and exploring optimal treatment strategies. This review gives an overview of the major advances that have been achieved to develop protocols to generate neoantigen TCR-T from T-iPSCs. We will also discuss the potentials and challenges they face in the treatment of hepatocellular carcinoma.